Postgraduate students’ difficulties and strategies on speaking - Devika Adelita; Sholihatul Hamidah Daulay (Universitas Ahmad Dahlan, 2023)
In both first and second language acquisition environments, speaking is one of the four macro skills that must be cultivated as a way of effective communication. This study was aimed to explore the postgraduate students' perception of speaking skills and to examine the most dominant problems faced by the postgraduate students in speaking. As a result of this issue, a qualitative research design was developed as an action study in a regular course. Therefore, the subjects of this research were 10 postgraduate students in the first semester at the State Islamic University of North Sumatera. The data were collected by a questionnaire which applied in Google form. The researcher shared the Google form link with the students via WhatsApp message. In analyzing data, the researcher analyzed the data based on each question and answer of the respondent. The researcher analyzed the data one by one to get the point of the research. After that, the whole data are discussed using the theory and continued by concluding. The result shows that it was found that the post-graduate students faced many problems in speaking in the target language, such, pronunciation, grammar, vocabulary, fluency, and speaking. There were also other problems such as lack of confidence and did not have any brave to speak in the second language.